2011
DOI: 10.1021/cg101547r
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Data Set for Structure−Property Investigations: Solubility and Solid-State Structure of Alkaline Earth Metal Salts of Benzoates

Abstract: A new resource for studying structure property relationships is presented, namely a systematic database of 36 organic salt structures together with phase specific aqueous solubility data. The salts are derived from four M2+ cations (Mg2+, Ca2+, Sr2+, Ba2+) and nine substituted benzoate anions. The intrinsic solubility of the free acid is found to have a major contribution to make to salt solubility, but despite previous literature assertions, there appears to be little correlation of solubility with the polari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
54
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(58 citation statements)
references
References 44 publications
3
54
1
Order By: Relevance
“…Thecomplex cations are each hydrogen-bonded to lattice water molecules to form two-dimensional cationic layers parallel to (001) with d(O···O) =2 .640 -3 .010 Åa nd ÐO-H···O =149°-175°. The observed bond lengths and angles of the 4-nba anion are in the normalrange and are comparable with those reported for compounds containing the free 4-nba anion [7,8]. The structure can be envisaged as one in which layers of cations alternatewithlayersofanions, and the layers are linked by hydrogen bonds(d(O···O)=2.640-3.010 Åand ÐO-H···O = 149°-175°), giving rise to at hree-dimensional supramolecular network.…”
Section: Methodssupporting
confidence: 75%
“…Thecomplex cations are each hydrogen-bonded to lattice water molecules to form two-dimensional cationic layers parallel to (001) with d(O···O) =2 .640 -3 .010 Åa nd ÐO-H···O =149°-175°. The observed bond lengths and angles of the 4-nba anion are in the normalrange and are comparable with those reported for compounds containing the free 4-nba anion [7,8]. The structure can be envisaged as one in which layers of cations alternatewithlayersofanions, and the layers are linked by hydrogen bonds(d(O···O)=2.640-3.010 Åand ÐO-H···O = 149°-175°), giving rise to at hree-dimensional supramolecular network.…”
Section: Methodssupporting
confidence: 75%
“…This last observation is surprising because many previous studies have shown correlation between these two features for both salt and cocrystal forms. [15,34,35] Measurement of solubility is notoriously variable and observed results are highly dependent upon method used. [36] The free acid solubility values used here were averages taken from a literature compendium rather than measured using a similar method to that used for the salt forms.…”
Section: Correlation Of Physical Properties For (1r2s)(-) Methylephementioning
confidence: 99%
“…[7][8][9][10][11][12][13][14] Some larger structural datasets are now available, such as the aqueous solubility data reported for 36 benzoate salts, [15] and the work of Davey and co-workers who structurally characterised 17 salt forms of the phenylethylamine base ephedrine and thoroughly analysed the inter-relationships of several properties including solubility. [16,17] Our interest in structure-solubility relationships and the existence of priorsystematic structural analysese of phenylethylamine bases, [15,18,19] including the work of Davey, prompted us to investigate solubility relationships in salt forms of methylephedrine. Herein we report aqueous solubility measurements on 51 salt forms, all of which have been characterised by single crystal diffraction and report on the relationships of solubility with, amongst other things, melting point, structure…”
Section: Introductionmentioning
confidence: 99%
“…The crystal structure of triethylammonium benzoate salt is similar to that of its analogue salicylic salts [1,2]. Among the complex intermolecular interactions [3,4], the most important hydrogen bonding is N1-H1×××O2 (bond length 2.744 (2) .I na ddition, the hydrogen bonds O4-H4D×××O2 and O3-H3B×××O1 (bond lengths 2.58(2) Åa nd 2.68(2) Åand bond angles 163.25°and 162.4°, respectively) are another important force to stabilize the crystal structure [5]. …”
mentioning
confidence: 79%